Factors Associated with Pap Smear Implementation among Women Referring to Healthcare Centers in Fasa, Iran: An Application of Theory of Planned Behavior - Zahra Moradi; Parvin Moradi; Ali Khani Jeihooni; Azizollah Dehghan (Hamadan University of Medical Sciences, 2017)
Background and Objective: Cervical cancer is the second most common cancer among the females. This cancer is considered as a preventable disease due to having a long period before the invasion, availability of appropriate screening program, and effective treatment of primary lesions. The aim of this study was to determine the factors related to per forming regular Pap smear test based on the Theory of Planned Behavior (TPB) among the females living in Fasa, Iran. Materials and Methods: This descriptive-analytic cross-sectional study was conducted on 700 married women in Fasa city in 2016. The study population was selected from the females referring to the healthcare centers of Fasa using simple random sampling technique. The data were collected by means of a three-part questionnaire, including demographic data, knowledge, and TPB constructs. Data analysis was performed using Pearson correlation coefficient test and logistic regression in SPSS, version 22. Results: According to the results, 45.7% of the patients had a history of undergoing a Pap smear test, and 20.7% of them performed this test regularly. The results indicated that knowledge, attitude, subjective norms, and perceived behavioral control were the predictors of intention and behavior of Pap smear test among the women (P<0.05). These components accounted for 57.4% and 31.6% of the intention and behavior variance, respectively. Conclusion: As the findings of this study indicated, it is possible to increase the level of screening behaviors among the women by improving their awareness, attitude, subjective norms, and perceived behavioral control. This measure in turn plays a significant role in the prevention and control of cervical cancer.